2019
DOI: 10.1021/acs.joc.9b02352
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Aryl Fluorosulfates into the Realm of Catellani Reaction Substrates

Abstract: Application of activated phenol fluorosulfates as substrates in a Pd/NBE mediated sequential alkylation-arylation, commonly known as a Catellani reaction, is presented. These substrates provide a level of complementarity to the commonly used aryl halides and, in combination with a plethora of existing Catellani reaction variations, enable even wider application of this powerful synthetic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In a significant contribution in this field, Bieliūnas and De Borggraeve found that treatment of 2-substituted aryl fluorosulfonates 36 with aryl boronic acids 37 and primary alkyl halides 38 in the presence of Pd(OAc) 2 /norbornene (NBE)/K 2 CO 3 combination as catalytic system in DMF resulted in corresponding multisubstituted arenes 39 in modest to high yields ( Scheme 11 ). 27 The results indicated that the presence of at least one relatively strong electron-withdrawing substituents in the phenyl ring periphery of aryl fluorosulfonates was crucial for this Catellani-type reaction, while the use of compounds bearing weakly electron-withdrawing substituents led to poor yields. Incompatibility of the reaction with substrates possessing aldehyde or nitrile moieties at the 2-position, was another limitation which was reported by the authors for their methodology.…”
Section: Carbon–carbon Cross-coupling Reactionsmentioning
confidence: 98%
“…In a significant contribution in this field, Bieliūnas and De Borggraeve found that treatment of 2-substituted aryl fluorosulfonates 36 with aryl boronic acids 37 and primary alkyl halides 38 in the presence of Pd(OAc) 2 /norbornene (NBE)/K 2 CO 3 combination as catalytic system in DMF resulted in corresponding multisubstituted arenes 39 in modest to high yields ( Scheme 11 ). 27 The results indicated that the presence of at least one relatively strong electron-withdrawing substituents in the phenyl ring periphery of aryl fluorosulfonates was crucial for this Catellani-type reaction, while the use of compounds bearing weakly electron-withdrawing substituents led to poor yields. Incompatibility of the reaction with substrates possessing aldehyde or nitrile moieties at the 2-position, was another limitation which was reported by the authors for their methodology.…”
Section: Carbon–carbon Cross-coupling Reactionsmentioning
confidence: 98%
“…In 2019, De Borggraeve and co-workers reported the use of aryl fluorosulfonates in Catellani-type reactions with orthoalkylation/ipso-arylation. [55] Using phosphine ligand-free conditions with Pd(OAc) 2 as the catalyst, the authors tested different variations of aryl fluorosulfonates, alkyl halides and aryl boronic acids (Scheme 7). The reaction worked best with aryl fluorosulfonates bearing electron-withdrawing groups.…”
Section: Catellani Reactionmentioning
confidence: 99%
“…In 2019, Borggraeve and coworkers [97] introduced aryl and heterocyclic fluorosulfates into the Catellani reaction, a sequential alkylation‐arylation mediated by Pd/NBE. This three‐component cross‐coupling reaction was further carried out by combining phenols with fluorosulfonylation to access the polyfunctional products of phenols (Scheme 35).…”
Section: Metal‐mediated Cross‐coupling Reactions For (Hetero)aryl Flu...mentioning
confidence: 99%